IMPORTANCE OF INTEGRATED PROTECTION OF SMALL GRAINS IN INCREASING COMPETITIVENESS IN PRODUCTION - Mirjana Staletić; Milivoje Milovanović; Vladimir Perišić; Vera Đekić (Ekonomika Poljoprivrede (1979), 2011)
The growing increase of cost of inputs related to crop protection and the increasing competition in the international market contributed to the reduction of competitiveness and proftability of small grain producers from Serbia. Recent researches showed that any single measure of protection of plants, no matter how effcient is not suffcient to achieve complete success. That is why the concept of integrated protection program, which involves the active use of the complex of various measures to prevent the development of diseases and pests and provides for obtaining high, stable and high quality production, with as little as possible costs and pollution of the environment. This makes the whole system sustainable and more competitive as a result of significant reduction of inputs and in particular the need for plant protection. In integrated protection programe, and particularly in the system of organic agriculture, special attention is paid to the thresholds of the harmful effects of diseases, pests and weeds, in order to increase the effciency of their control.